2011
DOI: 10.1371/journal.pone.0019850
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Surfactant Structure-Toxicity Relationships: Implications for Surfactant Use in Sexually Transmitted Infection Prophylaxis and Contraception

Abstract: BackgroundThe need for woman-controlled, cheap, safe, effective, easy-to-use and easy-to-store topical applications for prophylaxis against sexually transmitted infections (STIs) makes surfactant-containing formulations an interesting option that requires a more fundamental knowledge concerning surfactant toxicology and structure-activity relationships.Methodology/Principal FindingsWe report in vitro effects of surfactant concentration, exposure time and structure on the viability of mammalian cell types typic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
75
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 121 publications
(80 citation statements)
references
References 55 publications
5
75
0
Order By: Relevance
“…Taken together, our results support the observations in other studies and indicate the necessity to use a complex test-organism battery to evaluate the toxicity of surface cleaning preparations thoroughly. The response of a single test-organism might serve only as a preliminary indicator of toxicity, which can not substitute the whole data set from various test organisms [9] It has been reported previously, that toxicity of surfactants often correlates with their CMC; this indicates that the toxicity is related to destabilization and/or destruction of cell membrane [11]. Most of the MICs acquired in our experiments are below SCP-1 CMC value showing that this is not always the case.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Taken together, our results support the observations in other studies and indicate the necessity to use a complex test-organism battery to evaluate the toxicity of surface cleaning preparations thoroughly. The response of a single test-organism might serve only as a preliminary indicator of toxicity, which can not substitute the whole data set from various test organisms [9] It has been reported previously, that toxicity of surfactants often correlates with their CMC; this indicates that the toxicity is related to destabilization and/or destruction of cell membrane [11]. Most of the MICs acquired in our experiments are below SCP-1 CMC value showing that this is not always the case.…”
Section: Discussionmentioning
confidence: 71%
“…It is emphasized that a battery of several tests is required to assess toxicity more thoroughly [9][10]. Toxicity values of the used surfactant often correlate with its critical micelle concentration (CMC) [11]. CMC is a concentration of surfactant or detergent at which it forms micelles.…”
Section: Introductionmentioning
confidence: 99%
“…The onset of cytotoxicity was shown to involve neither membrane disintegration, nor perforation, nor cell lysis, suggesting that the susceptible target had to be intracellular. The high values (6 Ͻ n Ͻ 9) of the Hill coefficients, n, in the logistic fits of our experimental toxicity data (5) suggested that QAC toxicity involved cooperative breakdown of several biochemical processes. The primary site(s) of QAC toxicity would therefore have to be of vital importance to the physiology of the cell.…”
mentioning
confidence: 67%
“…MDCK II cells were grown as previously described (5). After achieving complete polarization, the cells were exposed to different concentrations of C 10 TAB for 3 h. At the end of incubation, Opti-MEM medium containing surfactant was replaced by fresh cell culture medium without phenol red, and the viability and caspase 3/7 activity were assayed using an ApoLive-Glo multiplex assay, according to the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation